The Impact Of Organizational Climate On Institutional Performance. A Field Study On The General Electricity Corporation In Yemen (International Journal of Environmental Sciences, 2025)
This study investigates the effect of organizational climate on institutional performance within the Public Electricity Corporation of Yemen. Utilizing a quantitative descriptive research design, data were collected via a structured questionnaire. The study population consisted of employees in various managerial and technical roles at the General Electricity Corporation in Yemen (N = 896). A proportionally stratified random sample of 269 participants was selected, and responses were measured using a seven-point Likert scale. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS v.28). The results indicate a significant and direct influence of organizational climate on institutional performance, with certain dimensions demonstrating a particularly strong effect. Specifically, communication systems and work procedures emerged as pivotal determinants of superior institutional performance. The study recommends prioritizing the enhancement of communication systems, refinement of work procedures, and the development of effective incentive mechanisms to foster improved performance.